RADICAL ISLAM AND THE DERADICALIZATION STRATEGY: Reconstruction of Abdurrahman Wahid’s Thoughts - Ngainun Naim (Sayyid Ali Rahmatullah Tulungagung State Islamic University, 2017)
This paper discusses about radical Islam and the strategy of deradicalization according to Abdurrahman Wahid thought. The rapid development of radical Islam in post-New Order Era has emerged the worriedness among people. A number of efforts to discontinue the development of radical have been done; one of the efforts is through the deradicalization strategy. The data presented in this paper originated from the thoughts of Abdurrahman Wahid spread in many books, magazines and internet. The set of the thoughts was then analyzed to observe the perspectives of Abdurrahman Wahid about radical Islam and the of deradicalization strategy. Abdurrahman Wahid viewed that radical Islam has destroyed Islam. Such strategy of deradicalization has presented through the indigenization of Islam, the role of Islamic boarding school, maintaining the tradition and building the interaction and through the Islamic spirituality.